2002
DOI: 10.1080/10715760290019372
|View full text |Cite
|
Sign up to set email alerts
|

PGE 1 Protection against Apoptosis Induced by d -galactosamine is Not Related to the Modulation of Intracellular Free Radical Production in Primary Culture of Rat Hepatocytes

Abstract: D-galactosamine (D-GalN) toxicity is a useful experimental model of liver failure in human. It has been previously observed that PGE1 treatment reduced necrosis and apoptosis induced by D-GalN in rats. Primary cultured rat hepatocytes were used to evaluate if intracellular oxidative stress was involved during the induction of apoptosis and necrosis by D-GalN (0-40mM). Also, the present study investigated if PGE1 (1 microM) was equally potent reducing both types of cell death. The presence of hypodiploid cells,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
53
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 36 publications
6
53
0
1
Order By: Relevance
“…28) Quintero et al reported that intracellular free radical production gradually increases with GalN concentration in rat hepatocytes. 4) Furthermore, several reports have suggested that oxidative stress induced by GalN suppresses hepatic GSH levels in animal treatments. 27,29) In this study, GalN treatment caused elevation in serum TNF-and depletion in hepatic GSH levels, while serum TNF-and hepatic GSH levels in rats pre-administered PPE (400 mg) once daily for 8 d were unaffected by GalN treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28) Quintero et al reported that intracellular free radical production gradually increases with GalN concentration in rat hepatocytes. 4) Furthermore, several reports have suggested that oxidative stress induced by GalN suppresses hepatic GSH levels in animal treatments. 27,29) In this study, GalN treatment caused elevation in serum TNF-and depletion in hepatic GSH levels, while serum TNF-and hepatic GSH levels in rats pre-administered PPE (400 mg) once daily for 8 d were unaffected by GalN treatment.…”
Section: Discussionmentioning
confidence: 99%
“…2,3) Hepatic apoptosis and necrosis induced by GalN intoxication are involved in a free-radical dependent fashion in rat hepatocytes. 4) Several researchers have reported that polyphenols originating from grapes, red cabbage, black rice, and strawberries have a wide range of biological effects such as anti-hepatotoxic, 5) anti-inflammatory, 6) and anti-carcinogenic 7) activities. Furthermore, it has been reported that natural compounds can protect liver from GalNinduced toxicity.…”
mentioning
confidence: 99%
“…This in turn inhibits mRNA and protein syntheses, alters the composition of cellular membranes, and finally leads to cellular damage as a result of lipid peroxidation [18][19][20][21] . The hepatocyte death is represented as apoptosis and subsequently necrosis 22 in vivo 3,6,8,23 and in vitro 24 . Other mechanisms of the hepatotoxicity have been explained as follows.…”
Section: Discussionmentioning
confidence: 99%
“…It was also reported that a patient suffering from liver disease showed a decrease in the renal blood flow, indicating renal vasoconstriction (Guarner et al 1987). Sire et al (1983) reported that GalN damaged the enzymes involved in the transport of substrates into the mitochondria by raising caspase-3 and reactive oxygen radical levels (Quintero et al 2002) and, as a result, phospholipids composition of the membrane is modified (Sire et al 1983). Flavonoids, which are also a group of polyphenolic antioxidants, occur naturally in vegetables and fruits.…”
Section: Introductionmentioning
confidence: 99%